The SuUR gene influences the distribution of heterochromatic proteins HP1 and SU(VAR)3-9 on nurse cell polytene chromosomes of Drosophila melanogaster. - Koryakov, D.E.; Reuter, G.; Dimitri, P.; Zhimulev, I.F. (Chromosoma, 2006)
We have investigated the distribution of three heterochromatic proteins [SUppressor of UnderReplication (SUUR), heterochromatin protein 1 (HP1), and SU(VAR)3-9] in chromosomes of nurse cells (NCs) and have compared the data obtained with the distribution of the same proteins in salivary gland (SG) chromosomes. In NC chromosomes, the SU(VAR)3-9 protein was found in pericentric heterochromatin and at 223 sites on euchromatic arms, while in SG chromosomes, it was mainly restricted to the chromocenter. In NC chromosomes, the HP1 and SUUR proteins bind to 331 and 256 sites, respectively, which are almost twice the number of sites in SG chromosomes. The distribution of the HP1 and SU(VAR)3-9 proteins depends on the SuUR gene. A mutation in this gene results in a dramatic decrease in the amount of SU(VAR)3-9 binding sites in autosomes. In the X chromosome, these sites are relocated in comparison to the SuUR (+), and their total number only varies slightly. HP1 binding sites are redistributed in chromosomes of SuUR mutants, and their overall number did not change as considerably as SU(VAR)3-9. These data together point to an interaction of these three proteins in Drosophila NC chromosomes.